Karyomorphology, Meiotic Behaviours and Pollen Fertility of Calendula officinalis L. (Calenduleae- Asteraceae) - Mallick, Pushpa Karna (International Journal of Applied Sciences and Biotechnology, 2021)
The present study includes chromosome number, karyomorphology, meiotic behaviors and pollen fertility of the species Calendula officinalis L.collected from central Nepal was cytologically carried out using two percent aceto-orcein for somatic chromosome determination and one percent aceto-carmine for meiotic study. Pollen fertility was based on stainability test using Muntzing solution. Somatic chromosome number determined for this taxon were 2n=28, haploid chromosome number n=14 and pollen fertility found to be 84.4 percent in the present study. In karyotype analysis chromosome length ranged from 0.4 to 2.6 µm and mean length was 1.5 µm. Likewise, absolute length found to be 21.9 µm and karyotype formula obtained was M16+m4+ sm8. Three types of chromosomes centromere at middle point, at median region and at sub –median region were observed. Meiosis with regular and irregular behaviors was observed in this study. The variations in chromosome numbers, irregularities in meiotic behaviors, variations in karyomorphological structure and high fertility rate shows evolve nature of this species which play a great role in evolution. Pollen fertility was also affected by meiotic abnormalities. Int. J. Appl. Sci. Biotechnol. Vol 9(1): 75-79